Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702543
|View full text |Cite
|
Sign up to set email alerts
|

Selective Undo Support for Painting Applications

Abstract: Today's widely deployed painting applications use a linear undo model that allows users to backtrack previous operations in reverse chronological order. This undo model is not useful if the user has performed desired operations after undesired ones. Selective undo, in contrast, allows users to select specific operations in the past and only undo those, while keeping the remaining operations intact. Although selective undo has been widely explored in the context of text editing and object-oriented drawing, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(10 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Implication for Design: Provide feedback of user actions for both changes to the data/content and to the interface, and enable users to undo either type of action. Although recent work has widely explored 'Selective Undo' , where users can undo specific operations instead of backtracking in a linear manner [52,53], we recommend expanding the 'Undo' scope by distinguishing between undoing an operation that affects the data/content or merely undoing a selection. For example, the system could offer a feature such as 'My Past Actions' that could show the user a list of the features that they had selected along with whether a feature caused a change to their data/content or just to the interface.…”
Section: Chapter 6 Discussion and Implications For Designmentioning
confidence: 99%
“…Implication for Design: Provide feedback of user actions for both changes to the data/content and to the interface, and enable users to undo either type of action. Although recent work has widely explored 'Selective Undo' , where users can undo specific operations instead of backtracking in a linear manner [52,53], we recommend expanding the 'Undo' scope by distinguishing between undoing an operation that affects the data/content or merely undoing a selection. For example, the system could offer a feature such as 'My Past Actions' that could show the user a list of the features that they had selected along with whether a feature caused a change to their data/content or just to the interface.…”
Section: Chapter 6 Discussion and Implications For Designmentioning
confidence: 99%
“…We found that 48% (68 publications) are low complexity, i.e., contain one or two features or accomplish one or two types of specific tasks. Aquamarine [123] is an example of a CST with low complexity, as it provides one single feature-the ability to selectively undo single actions in creative applications, e.g., brush strokes, rather than sequentially stepping backwards as in the current linear undo model. CSTs with medium complexity, i.e., have multiple features and a semi-complex system, account for 43% (61 publications).…”
Section: Complexitymentioning
confidence: 99%
“…All past locations are accessible. Also, when a user invokes a reciprocal drag-and-drop action to restore a past position P of an object O, DND −1 adds the straight move between O's current location and P to the end of the history, in the spirit of the inverse model for selective undo (used in e.g., [Berlage 1994;Myers 1998;Yoon et al 2013]), rather than inserting all reciprocal moves after the corresponding moves in the history, as the script model (used in, e.g., [Kurlander and Feiner 1988;Myers et al 2015]) would have done.…”
Section: All Past Locations Of An Objectmentioning
confidence: 99%
“…As Flatland is a system intended to be used by several users, undo commands can also be region-based, regardless of when they happened. This concept of regional undo has also been applied to spreadsheet editors [Kawasaki and Igarashi 2004], interactive large displays [Seifried et al 2012], code editors [Yoon et al 2013], VLSI systems [Zhou and Imamiya 1997], sketch-based interfaces [Oe et al 2013] and painting applications [Myers et al 2015]. However, to support such an advanced model of undo, applications must take into account a complex system of dependencies and causal relationships.…”
Section: Undo Modelsmentioning
confidence: 99%
See 1 more Smart Citation